International volatility risk and Chinese stock return predictability. (February 2017) - Chen, Jian; Jiang, Fuwei; Liu, Yangshu; Tu, Jun
Highlights: The international volatility risks are negatively associated with contemporaneous Chinese daily overnight stock returns. The international volatility risks positively forecast next-day Chinese daytime stock returns. The US volatility risk plays a dominant role in forecasting Chinese daytime stock returns. High US volatility risk forecasts high Chinese domestic market volatility, low trading activity, and low market liquidity. Abstract: This paper investigates the predictive ability of international volatility risks for the daily Chinese stock market returns. We employ the innovations in implied volatility indexes of seven major international markets as our international volatility risk proxies. We find that international volatility risks are negatively associated with contemporaneous Chinese daily overnight stock returns, while positively forecast next-day Chinese daytime stock returns. The US volatility risk (ΔVIX) is particularly powerful in forecasting Chinese stock returns, and plays a dominant role relative to the other six international volatility measures. ΔVIX's forecasting power remains strong after controlling for Chinese domestic volatility and is robust in- and out-of-sample. Economically, high ΔVIX forecasts high Chinese domestic market volatility, low trading activity, and low market liquidity, indicating that both ICAPM and liquidity risk help to explain international volatility risks' predictive power for Chinese stock returns.